Penalizing the forgery of a work of art in the Polish legal system: notes de lege lata and postulates de lege ferenda - Anna Gerecka-Żołyńska (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2022)
The aim of the article is to justify the formulated postulate to separate in the Polish legal system an autonomous type of offence consisting in the counterfeiting, alteration or illegal reproduction of a work of art, which would comprehensively – similarly to the protection of monuments, or maybe even more broadly – cover the most important phases of this behaviour, taking into consideration also those of a secondary nature related to marketing the forgery or its distribution. The concept of ‘work of art’ has been narrowed down to works of plastic art for the purpose of the article and in this text is understood as an independent object separated from other objects of individual and independent specificity, being man-made, possessing aesthetic value, and expressing emotional qualities (Gołaszewska, Zarys estetyki. Warsaw 1986: 277). The most important problems connected with activation of criminal law protection in the event that a perpetrator engages in conduct commonly referred to as ‘forgery of a work of art’ are presented. The research was conducted primarily using the dogmatic method, and to a lesser extent the historical and comparative method. Finally, it is established that the system of legal interests surrounding the current art market rules makes it necessary for the scope of legal protection of a work of art, including a historical monument in case of forgery, to focus equally on the rights of purchasers – as it has been the case so far – but consideration should also be given to the rights of original creators, so that they can react effectively if they are violated. As a result, having identified the need for legislative intervention with regard to the crime of altering or forging an item and the crime of sale of a forgery, a proposal is formulated to modify the existing legal solutions.